THE SIGNIFICANCE OF STRUCTURAL FRACTURE OF LIMESTONE IN INDUCING SEISMIC ANISOTROPY IN KANTHAN HILLS, PERAK - MASYHUR, EKO MARCH HANDOKO (2019)
The velocity of seismic waves is controlled by the elastic properties of the medium of propagation. However, the elastic properties of rock are not homogeneous in different directions with the presence of geological discontinuities